Analisis Penerimaan Nilai Melalui Kepuasan Pelanggan Terhadap Niat Penggunaan Secara Berkelanjutan Mobile Payment - Muhammad Madsum Abdullah; Asep M Ramdan; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of value received on interest in sustainable use through customer satisfaction of mobile payment users (ovo) on students of Muhammadiyah University of Sukabumi. The study used primary data collected by distributing questionnaires via google-form to students of Muhammadiyah University of Sukabumi who used the ovo payment application as many as 358 samples determined by the cluster sampling method. The analysis technique used is path analysis with Spss 22 software with a significance level of 5%. The results obtained are the value received has a direct effect on customer satisfaction, the value received has no direct effect on sustainable use, customer satisfaction has a direct effect on sustainable use, and the value received indirectly affects sustainable use through customer satisfaction. The expected implication of this research is to improve the quality of value provided to customers in order to increase customer satisfaction which will encourage interest in sustainable use of ovo payment products/services. Keywords: Value received, customer satisfaction, sustainable use